UJI AKTIVITAS ANTIDIABETES EKSTRAK DAUN PACAR AIR (Impatiens balsamina L.) TERHADAP GINJAL TIKUS WISTAR (Rattus novergicus L.) YANG DIINDUKSI ALOKSAN - Fadillah, Nurul Maurito; Febriani, Husnarika; syukriah, Syukriah (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: Diabetes mellitus is a serious, "chronic" condition that occurs when there is an increase in a person's blood sugar levels because the body is unable to produce enough insulin hormones/cannot effectively use the insulin produced. A lack of insulin, or the inability of cells to respond to it, causes high blood glucose levels (hyperglycemia), which causes clinical indicators of diabetes. Methods: This research is an experimental study using a completely randomized design. Twenty-four male white rats were divided into 6 groups consisting of normal controls (KN) who received no treatment, negative controls (K-) who were injected with alloxan at a dose of 150 mg/kg BW, positive controls (K+) who were injected with alloxan at a dose of 150 mg/kg BW. kg BW and glibenclamide at a dose of 0.09 mg/200 g BW, Treatment 1 (P1) was injected with alloxan at a dose of 150 mg/kg BW and ethanol extract of water henna leaves at a dose of 450 mg/KG BW, Treatment 2 (P2) was injected with alloxan with a dose of 150 mg/kg BW and ethanol extract of water henna leaves with a dose of 500 mg/KG BW, Treatment 3 (P3) was injected with alloxan at a dose of 150 mg/kg BW and ethanol extract of water henna leaves with a dose of 550 mg/KG BW. Mice blood glucose levels were measured on days 0 (after alloxan induction), 3, 7, and 14. Before the measurements, the mice were fasted for 8 hours. Results: Research shows that administration of water henna leaf extract has a significant effect in reducing urea and creatinine levels, as well as improving kidney morphology. However, it could not prevent the alloxan-induced increase in kidney weight in white mice. Conclusion: Administration of henna leaf extract (Impatiens balsamina L.) at a dose of 500 mg/kg BW had a significant effect on reducing urea and creatinine levels in white rats induced by alloxan. Administration of water henna leaf extract (Impatiens balsamina L.) at a dose of 450 mg/kg BW had a significant effect in improving kidney morphology in alloxan-induced white rats, whereas the organ index of water henna leaf extract could not prevent the increase in kidney weight in white mice induced alloxan